Excessive use of antidepressants and anxiolytics among adolescents and young people (Research, Society and Development, 2022)
The preventive action of pharmacists can occur in over-the-counter and clinical pharmacy, in this aspect, the use of antidepressants by young people and adolescents occurs mainly as a result of psychological diseases, the main ones being depression and anxiety. However, there is a problem that involves the abusive use of these drugs and the negative effects on the body of these users. Therefore, the importance of patient awareness through pharmaceutical care and assistance. This study aims to analyze the use of antidepressants in young patients and adolescents to control depression and anxiety, highlighting the main effects of their excessive use. This is an integrative literature review in which the delimited consultation platforms are: Google Scholar, SciELO, LILACS and Institutional Repositories. For this, the following search descriptors were used: Antidepressant; Abusive Use of Medicines; Preventive Pharmacy; Youth and Adolescents. The application of some criteria was limited: temporality - articles published in 2017-2022; methodological – literary, integrative, systematic reviews and field research. In this aspect, it can be said that depression in adolescence is one of the main conditions acquired by young people, since among 4 adolescents1 they are affected by depressive symptoms, which is a serious health problem, mainly related to their environment. It is noteworthy that self-medication with antidepressants has become a common habit, which brings many public health concerns, hence the need for pharmaceutical intervention to raise awareness of the family and patients.